(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study is talking for the first time about in this region to document the archaeological sites at Tuzkhormato and surroundings. There are more than (19) archaeological sites which took two trends one of them is parallel to Aq-Su river, which starts from behind Tuzkhomato mountain and takes NE-SW direction at Shirash Tapa site and ending at Zeghaitoon river near the bridge of (Tikrit-Tuz) road, and another trend is perpendicular to the first one at about the mid-way distance of the first trend. Coordinations of (5) archaeological sites were located and studied, these sites are as a hill ranges in its shape between small to large and the broken pottery were spread widely on the surface of these sites and some of this pottery are colored, also there are chert cutter that is used as knives (at Tal-Al-Shaer) site only. These sites were uplifted from the surface level with uneven degree depending on the volume of the buildings at that site, and all the buildings were built from muds, so these buildings are weak to resist the climate. It is probable that all buildings were buried under these sites, and the destroyed pottery of pre-Islamic period was distributed over the archaeological sites. Only one site on the Tuzkhormato mountain built with blaster and gypsum rocks, this site is (Gawor Qalasi) which from (Sassanian) period. All these sites still are not studied geologically or geophysically for determination the ages of these sites or delineating the geometrical shapes of buried buildings or searching some of the precious things like gold or other things.